Influence of banking regulation and supervision on banks’ performance - Boubacar, Aminata Issoufi; Bans-Akutey, Anita (goodwood publishing, 2023)
Purpose: The specific objectives of this study were to examine the effect of supervision on bank performance, ascertain the effect of regulation on bank performance, and assess the challenges faced by banks in the implementation of bank regulations. Research Methodology: This study adopted a descriptive survey approach using data collected from all employees of a commercial bank in Accra Newtown. Data were analyzed using descriptive and inferential statistics from IBM SPSS Statistics 24. Results: A positive relationship was found between banking regulation and bank performance and between supervision and bank performance. The study identified poor communication, lack of resources, resistance to change, and inefficient processes as the major challenges faced by banks in implementing strategies and achieving their objectives. Limitations: This study was limited to a commercial bank in Ghana, thus making it inappropriate to generalize the results. Contribution: To improve communication, there is a need for closer collaboration between banks and external regulatory bodies considering the positive effect of bank regulation on bank performance. From this study, there is a need for continuous monitoring and evaluation of processes to ensure that banks comply with regulations. Practical Implications: There is a need to maintain and improve effective regulatory and supervisory frameworks, as they positively affect bank performance. Novelty: This study examines banking regulation and supervision of bank performance with evidence from a commercial bank in Accra New Town, a suburb of Accra in Ghana.